2018
DOI: 10.1152/ajpgi.00344.2017
|View full text |Cite
|
Sign up to set email alerts
|

Absence of leptin signaling allows fat accretion in cystic fibrosis mice

Abstract: Negative energy balance is a prevalent feature of cystic fibrosis (CF). Pancreatic insufficiency, elevated energy expenditure, lung disease, and malnutrition, all characteristic of CF, contribute to the negative energy balance causing low body-growth phenotype. As low body weight and body mass index strongly correlate with poor lung health and survival of patients with CF, improving energy balance is an important clinical goal (e.g., high-fat diet). CF mouse models also exhibit negative energy balance (growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…However, this interpretation is complicated since activity levels of CF mice in both assays are reduced as determined by total distance traveled. CF mice display higher resting energy expenditure and can result in less active mice 33,34 . This reduction in total activity is not changed in anyway by the depletion of Hdac6 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation is complicated since activity levels of CF mice in both assays are reduced as determined by total distance traveled. CF mice display higher resting energy expenditure and can result in less active mice 33,34 . This reduction in total activity is not changed in anyway by the depletion of Hdac6 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome low de novo lipogenesis and following CF patient recommendation of high-fat diet feeding, we fed CF mice a high-fat diet. We recently reported that high-fat diet feeding failed to improve growth and adiposity in CF mice (2). These observations suggest that the paucity of adipose tissue might be a consequence of multiple factors, such as poor substrate availability either from de novo pathways (via VLDL delivery) or chylomicron origin from intestinal absorption and/or developmental or other endocrine factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are inconsistent data regarding the leptin concentration CF patients, which indicates that there is dysregulation of leptin synthesis among CF patients. Studies in mice model of CF revealed increasing caloric intake while disrupting a metabolic regulatory system, leptin signaling, led to enhanced growth and significant fat stores ( 14 ). Furthermore, leptin disturbances also contribute to abnormal immune response as well as susceptibility to infections that are common in CF ( 15 ).…”
Section: Discussionmentioning
confidence: 99%